Economic Evaluation of FebriDx®: A Novel Rapid, Point-of-Care Test for Differentiation of Viral versus Bacterial Acute Respiratory Infection in the United States - Katherine Dick; John Schneider (Journal of Health Economics and Outcomes Research)
**Background:** Acute respiratory infections (ARIs) are commonly treated with antibiotics in outpatient settings, but many infections are caused by viruses and antibiotic treatment is therefore inappropriate. FebriDx®, a rapid point-of-care test that can differentiate viral from bacterial infections, can inform antibiotic treatment decisions.